Search for the doubly heavy baryon Ξ0+bc decaying to J/ψ Ξ0+c - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Chinese physics. C, High energy physics and nuclear physics, 2023)
A first search for the decay is performed by the LHCb experiment with a data sample of proton-proton collisions, corresponding to an integrated luminosity of 9 fb−1 recorded at centre-of-mass energies of 7, 8, and 13 TeV. Two peaking structures are seen with a local (global) significance of and standard deviations at masses of 6571 and 6694 MeV/, respectively. Upper limits are set on the baryon production cross-section times the branching fraction relative to that of the decay at centre-of-mass energies of 8 and 13 TeV, in the and in the rapidity and transverse-momentum ranges from 2.0 to 4.5 and 0 to , respectively. Upper limits are presented as a function of the mass and lifetime.